Application-Oriented Investigation of Parasitic Limitation on Multilevel Modulation of High-Speed VCSELs - Chenyu Liang; Wenjia Zhang; Qing Wang; Shun Yao; Zuyuan He (IEEE Photonics Journal, 2019)
In this paper, we present an application-oriented investigation of parasitic limitation on the large signal performance of VCSELs when multilevel modulation is applied. VCSELs with different damping are taken into consideration. The parasitic parameters are extracted by fitting the measured $S_{11}$ data toward a frequency of 40 GHz. In the large signal analysis, four-level pulse amplitude modulation (PAM-4) signaling is embedded into the tool of VCSEL integrated spatio-temporal advanced simulator (VISTAS) and analyzed with extracted parameters. The transmitter and dispersion eye closure quaternary (TDECQ) of the 50-Gb/s PAM-4 signals from VCSEL model is evaluated to understand the relationship between parasitic parameters and signal quality. It is found that the over-damped VCSEL would benefit from larger parasitic bandwidth for PAM-4 modulation while the under-damped VCSEL with moderate parasitic bandwidth would present the best large signal response for PAM-4 modulation. The results indicate that for multilevel modulation, the parasitic parameters need to be carefully designed according to the VCSEL intrinsic parameters to achieve better large signal performance. By co-optimizing the key parasitic parameters, the parasitic circuit design criteria for each type of VCSEL are provided to obtain the best large signal performance under multilevel modulation. The results could provide a designing guidance for VCSELs aiming at multilevel modulation applications.